O discurso político na constituição do sujeito presidente: uma análise dos pronunciamentos de Jair Bolsonaro em rede nacional de rádio e televisão nos anos 2019, 2020 e 2021 - Amaral, Liene Rodrigues Martins (2023)
The present work aims to analyze the discursive functioning of Jair Bolsonaro’s statements about the office of the president of the republic from official statements on the national network of radio and television in the years 2019, 2020, and 2021. Based on the theoretical-analytical method of Foucauldian Discursive Studies, we sought to understand the knowledge-power relations that constitute the discourses, in the case of the political sphere (political discourse), and how these relations participate in the constitution process of the subject President, producing truths about themselves. That is, in his own words, how Bolsonaro discursively constructs his own position as president. The corpus is composed of the 18 (eighteen) official pronouncements made by the then president, Jair Bolsonaro, from 2019 to 2021. These are taken as monument-statements, being analyzed in the beat between description and interpretation, in their historicity, in their due opacity, and in a way to relate them to the other statements. The analysis gesture sought to identify the discursive regularities present in this corpus in order to understand how Bolsonaro's statements and pronouncements discursively constitute the very position of President of the Republic. In this way, the following discursive regularities stood out: subject president who associates his position with a divine mission; science-denying president subject during the COVID-19 pandemic; neoliberal presiding subject in relation to economic policies under the discourse of a good shepherd; and, finally, presiding subject: (neither) God, (neither) Fatherland, (neither) Family.